Design and Simulation of MEMS Hemholtz Resonator for Acoustic Energy Harvester - Ab Rahim, Rosminazuin; Johari, Muhammad Jabrullah (IEEE, 2016)
An acoustic energy harvester using Helmholtz resonator with piezoelectric circular diaphragm has been studied using COMSOL Multiphysics 5.1. In this paper, multiple designs considerations for MEMS Helmholtz resonator and piezoelectric circular diaphragm including the length and radius of the tube, the radius of the cavity and the thickness of the circular piezoelectric cantilever have been studied and investigated by varying it’s size with 5 different values for each parts in order to find the best size for optimum output voltage. The input pressure have been set to 1Pa as default. The simulation results demonstrated that under the same condition, a higher output pressure can be formed by having smaller tube radius and bigger cavity radius of the Helmholtz resonator. On the other hand, the interaction between air pressure’s vibration and piezoelectric diaphragm plays an important role in determining the amount of harvested acoustic power and the position of piezoelectric circular diaphragm in the Helmholtz resonator is at the optimum when it is placed at the end of the resonator compared to at the beginning of the resonator’s tube.